Analysis of the Flipped Classroom Model Using Digital Media in Improving Students' Mathematical Communication Skills - Dinda Silvia Putri; Yus Mochamad Colily; Zukhrufurrohmah Zukhrufurrohmah (Mathematics Education Journal, 2023)
The flipped classroom model is a learning model in which activities usually carried out in class are changed to be carried out at home, such as material explanations by the teacher, and activities carried out at home are changed to be carried out at school, such as doing assignments. The research aims to describe the flipped classroom model using digital media to improve mathematical communication skills. This research is a qualitative descriptive study. The research subjects used were six junior high school students in Batu City. In the pretest and posttest, data collection techniques to determine students' mathematical communication abilities while observation to determine teacher activities in learning uses the flipped classroom model using digital media. The instruments used are test sheets and observation sheets. Data analysis techniques consist of data reduction, data presentation, and conclusion. The results showed that after using the flipped classroom model using digital media, there was an increase in mathematical communication skills. After learning according to the lesson plan, the results of observations were in the very good category. There was an increase of 53% in the indicator of the ability to write mathematical situations correctly and precisely. The indicator of the ability to write ideas or solve problems correctly and accurately increased by 33%, while the ability to write conclusions from problems using their language increased by 39%.